Evaluation of methenamine for urinary tract infection prevention in older adults: a review of the evidence - Amy Chwa; Kevin Kavanagh; Sunny Anne Linnebur; Danielle R. Fixen (SAGE Publishing, 2019)
Urinary tract infections (UTI) commonly occur in older adults and can lead to more severe, life-threatening infections. Physiological factors that change with age are thought to contribute to the increased frequency of UTI recurrence in older adults. Unfortunately, there are limited methods to prevent UTI in older adults, and utilization of antimicrobial agents for prevention can have many negative consequences. Methenamine has been proposed as a useful drug for the prevention of UTI as it works as a urinary antiseptic, safely producing formaldehyde to prevent bacterial growth while avoiding bacterial resistance. The objective of this review is to evaluate the existing literature and discuss the use of methenamine in older adults for prevention of UTI. A PubMed search was conducted to identify studies evaluating the effectiveness of methenamine to prevent UTI in older adults, and 10 publications were selected based on relevant criteria. Based on the literature, methenamine appears to be a safe and effective option to prevent UTI in older adults with recurrent UTI, genitourinary surgical procedures, and potentially long-term catheterization. Studies have not evaluated the safety of methenamine in patients with impaired renal function or CrCl <30 ml/min. When selecting a treatment approach to preventing UTI in older adults with adequate renal function, clinicians may consider methenamine as a viable option.